Geek-art : pop culture now - Olivri, Thomas ([Paris, France] : Cernunnos, 2016)
"This original anthology collects the work of over 80 illustrators, each showcasing a unique take on a beloved geek universe. Whether in the form of a drawing, painting, sculpt, or street art, each piece represents a one-of-a-kind love letter to the stories and characters that inspired it"-- page 4 of cover.
Keywords: Popular culture in art; Caricatures and cartoons; Graphic arts; Pop art